USING WHATSAPP AS AN INSTRUCTIONAL TOOL TO ENHANCE READING AND WRITING SKILLS: INDONESIAN EFL LEARNERS' PERCEPTION - Pininta Veronika Silalahi; Pariyanto Pariyanto (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
This study intends to examine Indonesian EFL learners’ perception of using WhatsApp as an instructional tool to improve reading and writing skills. Covid-19 pandemic has made online learning compulsory for both teachers and students in which it is such a novel experience of instructional mode for some. WhatsApp as a pedagogical tool is thought to be feasible and readily available for the students and teachers to use at any time. With its features and capabilities to send multimedia messages such as images, recordings, audio, videos, and PDF files, it is believed to be potential to be used as a pedagogical tool. A five-point Likert scale questionnaire (1=strongly disagree; 2=disagree; 3=neutral/no opinion; 4=agree; 5=strongly agree) was employed to answer the research question. The result shows that the students perceived that using WhatsApp as a pedagogical tool can enhance reading and writing skills (average response = 3,53). It indicates that as a pedagogical tool, WhatsApp can be taken into account to be integrated into online learning.